2021
DOI: 10.3389/fpubh.2021.626070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Plastic-Free Lifestyle on Urinary Bisphenol A Levels in School-Aged Children of Southern Italy: A Pilot Study

Abstract: Bisphenol A (BPA) is an endocrine disruptor (ED) frequently used in food packaging. BPA is used as a monomer in the manufacture of some food packaging. This study aimed to evaluate the urinary BPA concentration in an Italian pediatric cohort, testing the levels of this ED over a period of 6 months, evaluating the effects of a diet regimen with a reduction of Plastic Food Packaging (PFP). One hundred thirty Italian children were enrolled and divided into two groups “School Canteen” and “No School Canteen.” The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…These steps include reducing plastic contact of foods for children ( Edwards et al. 2021 ; Sessa et al. 2021 ; Trasande et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These steps include reducing plastic contact of foods for children ( Edwards et al. 2021 ; Sessa et al. 2021 ; Trasande et al.…”
Section: Discussionmentioning
confidence: 99%
“…Families can also take steps by following the recommendations offered for other child-relevant contaminants, which we believe are likely also effective for reducing NMP exposures. These steps include reducing plastic contact of foods for children (Edwards et al 2021;Sessa et al 2021;Trasande et al 2018), regular wetcleaning of the home (Rhoads et al 1999), and careful choice of safer personal care products and building materials (Giovanoulis et al 2019).…”
Section: Recommendationsmentioning
confidence: 99%
“…In this scenario, these new techniques, posed at the center between toxicology and genetics, allow the forensic team to reach a certain diagnosis of the cause of death and not to make mistakes [110][111][112]. In the same manner, further studies should be conducted in order to identify new molecular biomarkers that could be useful both for forensic purposes, such as the identification of the cause of death, and for the identification of abuse drugs [113][114][115].…”
Section: Discussionmentioning
confidence: 99%
“… 32–36 Considering the country where more than half of the authors were from as the country in which the study was conducted, five (38.46%) articles were conducted in the United States, 24 , 26–28 , 33 four (30.77%) from Europe (UK, 29 Poland, 31 the Netherlands, 32 Italy, 36 three (23.08%) from Korea, 25 , 34 and one (7.69%) from China. 30 When the academic domain of the study was identified through the journal title and the author’s major or affiliated institution, public health, 27 , 30 , 33 medicine, 26 , 32 , 36 nursing, 31 , 34 , 35 published three (23.08%) articles for each, and environmental science had two (15.38%) articles. 24 , 29 The rest were pharmacy 25 and kinesiology, 28 one (7.69%) for each.…”
Section: Resultsmentioning
confidence: 99%
“…For study designs, seven (53.85%) articles 24 , 26 , 27 , 29 , 31 , 33 , 35 used one-group pretest-posttest design, three (23.08%) used randomized controlled trial design, 25 , 28 , 34 and there were one (7.69%) for each of randomized crossover design, 30 randomized factorial design, 32 non-equivalent control group pretest-posttest design. 36 …”
Section: Resultsmentioning
confidence: 99%